Case 3802: Proposal to remove Dicynodon turpior Huene, 1935 (Synapsida, Dicynodontia) from the Official List of Specific Names in Zoology and place Diodontosaurus pedroanum Tupi-Caldas, 1936 on the Official Index of Rejected and Invalid Specific Names in Zoology. - Demirjian, Vahe D (Bulletin of Zoological Nomenclature)
Noticed in BZN 76 (30 Aug 2019): 98.